Towards student wellness in the new teaching/learning process of Power Electronics - Trujillo-Aguilera, Davinia; Pozo-Ruz, Ana; Martín Graciani, María Olvido; Sánchez-Rodríguez, José (My University, 2014)
Nowadays, university education has undergone a significant change to new models that encourage the active role of students in the learning process. Moreover, the European Higher Education Area means an important change in the teaching/learning process: it is necessary to involve more efficiently to the students and encourage their independent study and active participation. This new framework includes the increase in the development and use of new Information and Communication Technology in education and the analysis of the academic performance of students and their sensation of engagement and burnout. In the particular case of Power Electronics, a new teaching methodology, based on a set of new software multimedia interactive tools, is designed and developed to use for the teaching and learning of this subject. The evaluation process consists of several questionnaires: for both students and lecturers, in order to evaluate the quality of these multimedia interactive tools; and only for students, so as to check their stress levels. This subjective information will be complemented with a detailed analysis of the obtained marks of the students and with the sensation of engagement and burnout, measured in terms of academic stress. Finally, a comparison between theses students and the previous ones that could not use these new educational tools will determine the achievement of the foreseen objectives.
Keywords: Enseñanza superior - Innovaciones tecnológicas; Evaluación de software educativo; E-learning; Electrónica de Potencia; Estrés académico